Evaluation of oral hygiene index, monitoring and oral hygiene instruction in visually impaired people - Jackyeli Windmuller; Rafaela Araujo Mendes; Sheila de Carvalho Stroppa; Juliana Yassue Barbosa da Silva (Revista Sul-Brasileira de Odontologia, 2015)
Eyesight can be considered a major human interaction promoter in motor, perceptual and mental activities and its loss can cause social environment changes. Objective: To evaluate and determine Simplified Oral Hygiene Index (OHI-S) in visually impaired individuals, as well as to provide information to promote oral health, to verify the effectiveness of educational activities for index change and to promote the social inclusion of visually impaired people. Material and methods: Study population was constituted by 28 visually impaired people of both genders, aged from 14 to 75 years old, residents and students at the Parana Institute for the Blind (IPC), Curitiba (PR, Brazil). The study was conducted in three stages. At first, the participants individually answered a questionnaire, performed tooth brushing and then the disclosure of oral biofilm was made, as well as the evaluation of Simplified Oral Hygiene Index, oral hygiene instruction and supervised toothbrushing. The second step was performed after seven days and the third after thirty days to reassess the Simplified Oral Hygiene Index to check whether there would a change in their values. Participants were divided into two groups according to Simplified Oral Hygiene Index: those who had only bacterial plaque and those who had plaque and calculus. Results: At the first day, patients with plaque and calculus had initial OHI-S mean of 2.3 (regular), 2.1 (regular) after seven days, and 2.4 (regular) after one month. Patients with only plaque at the first day had an average OHI-S of 0.71 (regular), 0.74 (regular) after seven days, and 0.78 (regular) after one month. Conclusion: Within this context, it is possible to understand that it is necessary to implement frequent supervised toothbrushing, oral instruction and motivation activities to promote wellness and health for these patients.